A systematic literature review on cyberstalking. An analysis of past achievements and future promises - Kaur Puneet; Dhir Amandeep; Tandon Anushree; Alzeiby Ebtesam A.; Abohassan Abeer Ahmed (Elsevier, 2022)
Individuals’ excessive use of technology-enabled communication platforms, such as social media, has led to scholarly recognition of rising incidences of cyberstalking. Despite considerable studies directed at its examination, the current research on cyberstalking is limited by a lack of clarity on its characterization and prevalence, coupled with a fragmented research focus. To address this limitation, a Systematic Literature Review (SLR) on cyberstalking has been undertaken. Rigorous protocols were applied to identify 49 empirical studies via Scopus and Web of Science, based on specific keywords and article selection criteria. Findings reveal four emergent research themes on characteristics and roles of cyberstalkers, victims, parents, social media, and online service providers, as well as reporting, coping, and prevention strategies discussed in prior studies. Findings imply the need for temporal and cross-cultural validation of measurement scales and prior results by developing sophisticated, theoretically-grounded frameworks. Based on study findings, a research framework is proposed to assist researchers in future examinations of under-investigated associations and constructs. Implications arise for studying potential pre-emptive factors to address cyberstalking at a societal level by disseminating appropriate information to the general public. There is a need to develop stringent legislation and to induce service providers' active participation to prevent cyberstalking.